Tailoring the time delay of deployable structures using the Intermediate Axis Theorem - Bentley, Christopher S.; Butler, Jared; Harne, Ryan L. (Engineering structures, 2024)
Deployment techniques devised from compliant joints, shape memory materials, and inertial effects from rotational motion can be employed in deployable structures to realize a time delay in deployment. Some of these deployment techniques require additional components to generate a time delay or are subject to premature failure caused by harsh environments. To surmount these limitations, this research proposes a method that tailors time-delayed structural deployment that is driven by the Intermediate Axis Theorem, where rotation about the intermediate axis generates a time delay in deployment before the structure tumbles and inertial effects instigate expansion. The proposed method requires that the deployable structures have three unique principal moments of inertia in the compacted configuration. Numerical results are generated to explore the influence of the rate of rotation and geometry on time delay in structural deployment. A physical prototype demonstrates the plausibility of applying the proposed method. The results in this study encourage broader exploration of passive deployment techniques with physical time delays in deployment inspired from the Intermediate Axis Theorem. •We explore applications of the intermediate axis theorem.•Deploying structures are a prime use for the phenomenon.•Intermediate axis theorem can be used to tailor deployment.